Divine metaphors in selected Hebrew Psalms of Lamentation - Basson, Alec 1973- (Tübingen Mohr Siebeck, 2006)
Alec Basson untersucht aus einer kognitiv-anthropologischen Perspektive Metaphern des Göttlichen anhand einer Auswahl von Klagepsalmen aus dem Alten Testament. Er argumeniert, daß die gegebene Textinformation mehr als nur eine rein literarische ist. Sie ist auch eine kognitive Darstellung der Welt des Psalmendichters. In Notsituationen verwendet der Dichter verschiedene kognitive Strategien wie kulturelle Modelle, Bildschemata und begriffliche Metaphern als ein Mittel, um die Gottheit darzustellen. Die Untersuchung zeigt die Verbindung zwischen der kulturellen Erfahrung des Psalmendichters, seinem kognitiven Konstrukt der Realität und der metaphorischen Darstellung. Um die göttlichen Metaphern, die in den Klagepsalmen vorkommen, gerecht zu werden, muß die kognitive Welt des Psalmendichters mitberücksichtigt werden. - Alec Basson examines the divine metaphors in a selection of biblical Hebrew Psalms of Lamentation from a cognitive-anthropological perspective. He argues that the textual information in these poems is more than literary information as such; it is also a cognitive representation of the psalmist`s world. In situations of affliction, the poet employs various cognitive strategies viz. cultural models, image-schemas and conceptual metaphors as a means of portraying the deity. The exploration illustrates the link between the psalmist`s cultural experience, cognitive construal of reality and the metaphorical representations. To appreciate fully the divine metaphors used in the Psalms of Lamentation, one has to examine the cognitive world of the poet.
Teilw. zugl.: Stellenbosch, Univ., Diss., 2005
Archivierung/Langzeitarchivierung gewährleistet
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Language, style; Bibel; Bibel; Bibel; Bibel; Bibel; Bibel; Bibel; Bibel; Laments in the Bible; Metaphor in the Bible; Psalter; Metapher; Klagelied; Hochschulschrift